Policing unacceptable protest in England and Wales: A case study of the policing of anti-fracking protests. (February 2019) - Jackson, Will; Gilmore, Joanna; Monk, Helen
In recent years public order policing policy in England and Wales has undergone significant changes. A 'human rights compliant' model of protest policing has been developed since 2009 and this article makes a contribution to the body of academic work considering the impact of these changes on operational policing. Drawing upon a longitudinal case study of the policing of protests against 'fracking' in Salford, Greater Manchester, in 2013–14, the article contrasts post-2009 policy and academic discourses on protest policing with the experiences of anti-fracking protesters. To develop this assessment, the article also draws attention to previously unexplored definitions of acceptable and unacceptable protest set out by police in more recent policy, and considers the extent to which these definitions are reflected in the police response to anti-fracking protest. The article suggests that a police commitment to a human rights approach to protest facilitation is, at least in the case of anti-fracking protest, contingent on the focus and form of political activism.